2020
DOI: 10.32473/edis-ss689-2020
|View full text |Cite
|
Sign up to set email alerts
|

Hemp Fertilization: Current Knowledge, Gaps and Efforts in Florida: A 2020 Report

Abstract: Hemp is an annual herbaceous plant that may be grown for fiber, seed, or flowers. Starting in April 2020, the Florida Department of Agriculture and Consumer Services began accepting applications for cultivation of hemp in Florida, with the potential for building a $20–$30 billion industry in the state. The statewide UF/IFAS Industrial Hemp Pilot Project is researching aspects of agronomic production for hemp cultivation. While a few other state soil testing laboratories provide soil tests and nutrient recommen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A resurgence in hemp cultivation is seen since the European Union and the US, and other countries, have legalized the cultivation of industrial hemp, and many other countries have reintroduced hemp cultivation with low THC levels [ 23 ]. For example, from 2020 Florida Department of Agriculture and Consumer Services is allowing its cultivation with the potential of building a $20–$30 billion industry in the state [ 27 ] whereas Europe observed a record amount of hemp cultivation amounting to 33,000 ha in 2016 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…A resurgence in hemp cultivation is seen since the European Union and the US, and other countries, have legalized the cultivation of industrial hemp, and many other countries have reintroduced hemp cultivation with low THC levels [ 23 ]. For example, from 2020 Florida Department of Agriculture and Consumer Services is allowing its cultivation with the potential of building a $20–$30 billion industry in the state [ 27 ] whereas Europe observed a record amount of hemp cultivation amounting to 33,000 ha in 2016 [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different grain, flower, or fiber hemp production systems may require differing N recommendations based on the final production goal and environmental conditions (Fike, 2016;Kaur et al, 2023). Literature has shown that the N requirement for grain and flower production is higher than fiber production (high N reduces fiber quality) (Fike, 2016;Kaur et al, 2023;Mylavarapu et al, 2020). Therefore, optimizing N fertilization for different economic products obtained from hemp is essential.…”
Section: Introductionmentioning
confidence: 99%
“…While best management practices have been adopted for other agronomic crops, there has yet to be any previous research available on hemp nutrient management to develop best management practices for hemp in Florida. Currently, P and K recommendations in hemp production follow the guidance of non‐irrigated corn production in Florida (Mylavarapu et al., 2020). Due to high N losses because of heavy rainfall and sandy soils in Florida (Sartain, 2009; Shober & Mylavarapu, 2012), N fertilization recommendations are not based on soil testing but are developed on a research basis (Mylavarapu et al., 2008).…”
Section: Introductionmentioning
confidence: 99%